More Female Arbitrators? Gender Equality in Arbitral Tribunals - Herrada Sánchez, Tatiana (2020)
In the last decades, different public and private initiatives for closing gender-gaps in professional environments have been designed, presented and implemented. Likewise, these initiatives also aim to progressively strengthen female representation on the aforementioned environments. However, some fields are still far from reflecting the real level of presence or sufficient representation of women, as is the case of arbitration.In this article, the author analyzes and contextualizes the importance of this issue through data collected and elaborated from national and international institutions in order to show how many women are effectively appointed in arbitral tribunals and who are the actors involved in this process. Thus, although the presence of more women in the professional scene could be beneficial to achieve a diversity of perspectives in the arbitration process, it is also necessary to identify, mitigate and/or solve the issues that prevent more equitable spaces.